Design and analysis of distance error correction–based localization algorithm for wireless sensor networks. Issue 12 (28th November 2018) - Prashar, Deepak; Jyoti, Kiran; Kumar, Dilip
Abstract: Localization error is the main criteria to decide the efficiency on any localization approach. In case of range‐free hop‐based localization approaches, position coordinates estimation is done through the common steps like the calculation of the minimum hop count, hop size, and then later on applying the multilateration or least square approach. There are many improvements that have been made in the form of various algorithms through some changes in the common steps for the reduction of localization error. It has been observed that the existing algorithms are still having the highest value of localization error. To overcome the deficiencies in the existing algorithms, a novel distance error correction metric–based approach has been introduced. This paper presents a distance error correction–based algorithm (DEC‐hop) for the hop‐based localization approach for a wireless sensor network. Distance‐based error correction factor that is introduced in this paper further reduces the localization error value to some extent. For measuring the effectiveness and the preciseness of the given approach, it is inspected with other improved algorithms based on DV‐hop. Simulation results have confirmed that the proposed error correction–based algorithm outperforms the other variety of improved hop‐based algorithms. Results are analyzed in terms of various factors like the localization error, accuracy, and error variance against the parameters of interest taken as node amount, anchor ratio, and communication range of the node. Abstract : This work presents a distance error correction–based algorithm (DEC‐hop) for the hop‐based localization approach for a wireless sensor network. It is inspected with other improved algorithms based on the DV‐hop. Results are analyzed in terms of various factors like the localization error, accuracy, and error variance against the parameters of interest taken as node amount, anchor ratio, and communication range of the node. Also, the statistical analysis is being done for each one of the comparison.